Glabridin attenuates antiadipogenic activity induced by 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin in murine 3T3‐L1 adipocytes. Issue 11 (26th July 2018) - Choi, Eun Mi; Suh, Kwang Sik; Jung, Woon‐Won; Park, So Young; Chin, Sang Ouk; Rhee, Sang Youl; Kim Pak, Youngmi; Chon, Suk
Abstract: 2, 3, 7, 8‐Tetrachlorodibenzo‐p‐dioxin (TCDD) has various toxicological effects in adipose tissue. Evidence is accumulating that glabridin, a flavonoid extracted from licorice, has beneficial effects on the regulation of glucose homeostasis. In this study, we investigated whether glabridin suppresses TCDD‐induced loss of adipogenic action using 3T3‐L1 adipocytes as a cell culture model of wasting syndrome. Glabridin effectively suppressed TCDD‐induced loss of lipid accumulation in this model. Pretreating cells with glabridin increased the gene expression of not only the adipogenesis‐associated key transcription factors peroxisome proliferator‐activated receptor gamma (PPARγ) and CCAAT/enhancer binding protein alpha, but also lipoprotein lipase in the presence of TCDD. TCDD decreased insulin‐stimulated glucose uptake, which was effectively restored by pretreatment with glabridin. Glabridin also inhibited the TCDD‐driven decreased production of insulin receptor substrate 1 and glucose transporter 4. TCDD increased the production of mitochondrial superoxides, prostaglandin E2, phospholipase A2, cyclooxygenase‐1 and intracellular calcium concentrations, while reducing the production of PPARγ coactivator 1 alpha and glycolysis. However, glabridin treatment reduced these TCDD‐induced effects. We conclude that glabridin suppresses the TCDD‐induced loss of lipid accumulation in 3T3‐L1 adipocytes by regulating the levels of PPARγ, CCAAT/enhancer binding protein alpha, lipoprotein lipase, glucose uptake, prostaglandin E2 and energy metabolism. These results also provide in vitro evidence of the effects of glabridin on adipocyte metabolism, which suggests a protective effect against dioxin exposure in the development of insulin resistance and diabetes. Abstract : Glabridin suppresses the TCDD‐induced loss of lipid accumulation in 3T3‐L1 adipocytes by regulating the levels of PPARγ, CCAAT/enhancer binding protein alpha, lipoprotein lipase, glucose uptake, prostaglandin E2 and energy metabolism. These results provide in vitro evidence of the effects of glabridin on adipocyte metabolism, which suggests a protective effect against TCDD exposure in the development of insulin resistance and diabetes.